Chompy has a friend for lunch - Satterthwaite, Mark; Eboli, Pedro (New York, NY : Scholastic Inc., 2023)
Can kids and monsters become friends? Adorable monster Chompy REALLY wants to find out in this interactive book! Hi! I'm Chompy! Thanks for having a playdate with me! Yes, I'm a monster. And monsters SOMETIMES eat people. But not me! I only want to be FRIENDS. And you're so FUN! Will you be my friend? But, what smells so delicious? GASP! Is it YOU? Uh oh...
K-3
Keywords: Monsters -- Juvenile fiction; Friendship -- Juvenile fiction; Hunger -- Juvenile fiction; Humorous stories; Monsters -- Fiction; Friendship -- Fiction; Hunger -- Fiction; Humorous fiction; Toy and movable books; Lift-the-flap books